Prevalence of back pain in German elite handball players - Surmann, C.; Fett, D.; Trompeter, K.; Platen, P. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Back Pain is one of the most occurring complaints in sports. Handball is a very intensive contact sport that is associated with mechanical strain on the musculoskeletal system. Especially elite handball players are physically stressed due to high training volume and competition. Consequently this might be related with the development of back pain. This study aims to determine lifetime prevalence (LP) and point prevalence (PP) of back pain in German elite handball players regarding the localization at the spine. Methods: N=32 handball players (m=8, f=24, 18.4±2.0 yrs, 177.2±7.8 cm, 71.8±9.5 kg, training volume: 13.8±4.1 hours/week) were asked to fill in an online-questionnaire based on valid Nordic Questionnaire by Kuorinka et al. (1987).Additionally, training volume was collected. X2-statistics were used to determine differences in back pain between sexes, the pearson correlation coefficient was used for analyzing it´s relation to age, training volume, body weight and height. Results: LP of back pain was 84.4%. Regarding different parts of the spine the LP of pain was 53.1% in the neck, 28.1% in the thoracic spine and 81.3% in the lumbar spine. PP of pain in the total back was 25.0% (neck: 15.6%, thoracic: 6.3%, lumbar: 25.0%). Comparison between sexes showed no significant differences. There was a statistical significant correlation for age and PP of low back pain as well as for age andPP of neck pain (p<.05) in female handball players. Also for the females training volume and LP of low back pain showed a correlation (p<.05). For male players no significant correlations were found. Discussion: The results indicate that back pain is a great problem in German elite handball players. Nearly 85% of investigated handball players hadback pain at least once in their life. Especially low back pain seems to be problematical in this sample. This is in line with findings in the literature. Tunas et al. (2015) found LPand PP of low back pain in female handball players to be 63% and 26%. In the presentinvestigationLP was much higher compared to this data. One possible reason could be the high competition level of the sample. The results underline the necessity of back pain prevention in elite handball players. Acknowledgement: The study was supported by the Federal Institute for Sport Science, Germany (ZMVI1-080102A/11-18).